2019
DOI: 10.1108/jedt-10-2018-0179
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of crack in beams using anti-resonance technique and FEA approach

Abstract: Purpose In the case of machines, structures and assemblies, the crack generation and propagation is becoming a great concern, especially in airplane wings, turbine blades and such other applications. This is because these parts are very large in size and the crack size is very small, i.e. in microns. Hence, there is an important need to locate the crack and to find its severity before it starts to propagate and also to detect these parameters by on-site non-destructive testing methods. This paper aims to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The crack propagation in machines, structures, and assemblies such as airplane wings, turbine blades, and other applications has a great interest to predict the operational life for machine components; then it is very important to identify the severity of crack before it starts to propagate. 22 Hence, inverse problem for detect crack severity, that is, crack depth prediction has been included in the study of crack severity. In this study, similar to Bhaurkar and Thakur, 22 results of FEA frequency ratio for the first mode of bending vibration for the cracked simply supported beam versus crack depth ratio are plotted as shown in Figures 28-30.…”
Section: Inverse Problem For Assessing Crack Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…The crack propagation in machines, structures, and assemblies such as airplane wings, turbine blades, and other applications has a great interest to predict the operational life for machine components; then it is very important to identify the severity of crack before it starts to propagate. 22 Hence, inverse problem for detect crack severity, that is, crack depth prediction has been included in the study of crack severity. In this study, similar to Bhaurkar and Thakur, 22 results of FEA frequency ratio for the first mode of bending vibration for the cracked simply supported beam versus crack depth ratio are plotted as shown in Figures 28-30.…”
Section: Inverse Problem For Assessing Crack Severitymentioning
confidence: 99%
“…22 Hence, inverse problem for detect crack severity, that is, crack depth prediction has been included in the study of crack severity. In this study, similar to Bhaurkar and Thakur, 22 results of FEA frequency ratio for the first mode of bending vibration for the cracked simply supported beam versus crack depth ratio are plotted as shown in Figures 28-30. It is observed that there is change in FEA frequency ratio as crack depth ratio changes where FEA frequency ratio decreases as crack depth ratio increases.…”
Section: Inverse Problem For Assessing Crack Severitymentioning
confidence: 99%
“…Previous studies also found that the upper sections of the structures are the most crucial as they are affected by both the soil stiffness, probable ground liquefaction characteristics (Wang et al , 2019) and structural motions (Rahnavard et al , 2018; Radkia et al , 2020; Etedali et al , 2020; Lanzi and Luco, 2018; Tsai et al , 2019). So, to predict these damage due to ground motion, various analytical approaches are adopted, such as a simplified single-degree-of-freedom system (Adam et al , 2004; Miranda and Akkar, 2003; Williamson, 2003; Takizawa et al , 1980), use of finite-element analysis to measure the structural response (Williamson, 2003; Takizawa et al , 1980; Bhaurkar and Thakur, 2019) and recently emerged incremental dynamic analysis (Zareian et al , 2010; Medina et al , 2006; Vamvatsikos and Cornell, 2002; Zareian et al , 2007; Moradipour et al , 2013). Dynamic analysis should have been carried out to determine the structure's nature and complete response against base excitation (Ahamad and Pratap, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Impact loading simulation on a construction safety helmet over a head form is carried out by Khan and Sonawane (2019) using 3D FE simulations. Bhaurkar and Thakur (2019) carried out a FE analysis for the investigation of crack in the beams. Barour and Zergua (2020) simulated reinforced concrete beams strengthened in shear with carbon fiber-reinforced polymer sheets under four-point bending using ANSYS software.…”
Section: Introductionmentioning
confidence: 99%